La ciudad colombiana : la formación espacial americana prehispánica - Aprile Gniset, Jacques (Colección Artes y Humanidades (Universidad del Valle). Urbanismo., 2016)
The author analyzes the role of the various forces involved in urban processes and its result in the occupation of the territories and the socio-spatial conformations. This second edition includes never before published graphic documents (drawings, maps and photographs) corresponding to the field work and archive of his permanent research on the process of urbanization in Colombia.